2014
DOI: 10.1177/0263276413510050
|View full text |Cite
|
Sign up to set email alerts
|

Vital Systems Security: Reflexive Biopolitics and the Government of Emergency

Abstract: This article describes the historical emergence of vital systems security, analyzing it as a significant mutation in biopolitical modernity. The story begins in the early 20th century, when planners and policy-makers recognized the increasing dependence of collective life on interlinked systems such as transportation, electricity, and water. Over the following decades, new security mechanisms were invented to mitigate the vulnerability of these vital systems. While these techniques were initially developed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(144 citation statements)
references
References 39 publications
0
139
0
5
Order By: Relevance
“…Anthropologists have shown that administrators and planners increasingly respond to this futurity and its dimension of risk through ‘prognosis’ (Mathews and Barnes, 2016), regimes of preparedness (Samimian‐Darash, 2009), and manipulations of time (Guyer, 2007). When they conflate disaster with national security, regimes of anticipation increase government control over spaces, populations, and bodies (Lakoff and Collier, 2008; Collier and Lakoff, 2015). When they aim to manage risk related to the materiality and unpredictability of nature, anticipatory models can affect the mobility of populations (Adey and Anderson, 2011).…”
Section: The Emotional Lives Of Disastersmentioning
confidence: 99%
“…Anthropologists have shown that administrators and planners increasingly respond to this futurity and its dimension of risk through ‘prognosis’ (Mathews and Barnes, 2016), regimes of preparedness (Samimian‐Darash, 2009), and manipulations of time (Guyer, 2007). When they conflate disaster with national security, regimes of anticipation increase government control over spaces, populations, and bodies (Lakoff and Collier, 2008; Collier and Lakoff, 2015). When they aim to manage risk related to the materiality and unpredictability of nature, anticipatory models can affect the mobility of populations (Adey and Anderson, 2011).…”
Section: The Emotional Lives Of Disastersmentioning
confidence: 99%
“…16 A similar point has been made by Stephen J. Collier and Andrew Lakoff (2014) in their genealogy of "vital systems security." They, too, suggest an alternative view of the emergence of "resilience" and its political implications relative to neoliberalism.…”
Section: Endnotesmentioning
confidence: 69%
“…It is instead the very global movement of animate and inanimate entities across boundaries, which has to be protected against immanent threats. The management of public health risks is therefore concerned primarily with what Collier and Lakoff (2014) have identified as 'vital systems'. It is attentive to those infrastructures, hubs and nodal points that 'operate' world traffic and realise global connectivities .…”
Section: Epidemic Spaces: Towards the Planetary Horizon Of Circulationmentioning
confidence: 99%